Creating inclusive libraries by applying universal design a guide - Spina, Carli (Library Information Technology Association (LITA) Guides, 2021)
"This book offers a thorough and engaging introduction to Universal Design and concrete examples of how these principles can be applied at libraries of all sizes, types, and budgets"--